Structure and thermal stability of a novel nanocomposite solar selective absorber coating. (December 2021) - Liu, Y.; Liu, H.D.; Pelenovich, Vasiliy; Li, J.Y.; Wan, Q.; Guo, J.L.; Chen, Y.M.; Zhang, J.; Li, Z.G.; Yang, B.
Abstract: Improving the utilization efficiency of solar energy requires effective high-temperature solar absorbers. However, the most current absorbers degrade at high working temperatures. Here, we report a novel TiN/(TiN/AlTiSiN)3 /AlTiSiON/AlTiSiO tandem absorber with excellent thermal stability up to 650 °C in air. The absorber was designed according to the optical constants of each layer which were obtained by modeling their experimental reflectance and transmittance spectra on the quartz substrates. Then the designed absorber was fabricated using arc ion plating, and its optical performance was manipulated by tuning the thickness of AlTiSiN. An optimized solar selectivity of 0.905/0.146 could be achieved on the as-deposited absorber, and the optical performance only slightly decreased with a performance criterion (PC) of 0.0215 after annealing treatment at 650 °C in air for 2 h. The dense amorphous AlTiSiO and AlTiSiON films can effectively hinder the oxygen diffusion to the inner absorber, and the nanocomposite and multilayer structure in the TiN/AlTiSiN absorber layer can limit atomic diffusion and grain growth, resulting in high thermal stability. These results indicate that the absorber can be a suitable potential candidate for high-temperature solar energy conversion applications. Highlights: A novel SS/TiN/(TiN/AlTiSiN)3 /AlTiSiON/AlTiSiO solar selective absorber was deposited by arc ion plating technique. The absorber had an optimized solar selective of 0.905/0.146. The absorber exhibited high thermal stability up to 650 °C in air.